Análise de desempenho de um motor ciclo otto a biometano em comparação com gasolina e etanol - Garlet, Roberto Antonio (2022)
The increasing use of fossil fuels and the growing demand for energy in recent decades have led to a major problem of greenhouse gas emissions and the causes of climate change. Therefore, efforts must be made to reduce carbon emissions from various sectors, including the transportation sector, which is one of the largest contributors to emissions. In addition to ethanol, gaseous fuels such as biogas and biomethane are also on the rise, as they can be produced by processing biomass and are therefore renewable. Experiments were performed to compeare the performance of biomethane , ethanol and gasoline in a single cylinder research engine with spark ignition and fuel injection at the intake port under different load conditions: 3 bar, 6 bar and 9 bar IMEP, at two differen t compression ratios: 11.6:1 and 14.3:1 and engine speed of 1800 rpm on a dynamometer. Due to similar properties and better availability, CNG was used to simulate biomethane operation. The results show that CNG has the lowest specific fuel consumption at all load conditions, outperforming gasoline and ethanol. combustion phase can also be adjusted The to the ideal condition with CNG, burning half of the fuel mass at about 8° after top dead center. At a compression ratio of 11.6:1 and a load of 9 bar IMEP, the efficiency of the gaseous fuel was about 34%, that of gasoline was 33%, and that of ethanol was 36%, while at a compression ratio of 14.3:1 with the same load, the efficiency with CNG increased to about 35%, while gasoline remained at about 33% and ethanol increased to about 37%. The gaseous fuel with a compression ratio of 11.6:1 at a load of 9 bar IMEP had the lowest NOx emission levels, which were about 13 g/kWh, while these emissions were 15 g/kWh for ethanol and 19 g/kWh for gasoline.